Understanding the Role of Mucosal-Associated Invariant T-Cells in Non-human Primate Models of HIV Infection - Barber-Axthelm, Isaac M.; Kent, Stephen J.; Juno, Jennifer A. (Frontiers in Immunology, 2020)
Chronic HIV infection causes systemic immune activation and dysregulation, resulting in the impairment of most T-cell subsets including MAIT cells. Multiple human cohort studies demonstrate MAIT cells are selectively depleted in the peripheral blood and lymphoid tissues during HIV infection, with incomplete restoration during suppressive antiretroviral therapy. Because MAIT cells play an important role in mucosal defense against a wide array of pathogens, fully reconstituting the MAIT cell compartment in ART-treated populations could improve immunity against co-infections. Nonhuman primates (NHPs) are a valuable, well-described animal model for HIV infection in humans. NHPs also maintain MAIT cell frequencies more comparable to humans, compared to other common animal models, and provide a unique opportunity to study MAIT cells in the circulation and mucosal tissues in a longitudinal manner. Only recently, however, have NHP MAIT cells been thoroughly characterized using macaque-specific MR1 tetramer reagents. Here we review the similarities and differences between MAIT cells in humans and NHPs as well as the impact of SIV/SHIV infection on MAIT cells and the potential implications for future research.